In‐Stream Nitrogen Dynamics in a Point Source Influenced Headwater Stream During Baseflow Conditions - Spill, Caroline; Ditzel, Lukas; Gassmann, Matthias (Water resources research, 2024)
Hydrochemical signatures are often traced back to their original sources using data collected at catchment outlets. However, this approach introduces uncertainties, as signals may add up, cancel each other out, or be subject to transformation processes. Specifically rural point sources, such as communal wastewater treatment plants (WWTPs), are often overlooked and remain poorly understood in terms of their (local) impact, on water quality and quantity dynamics. We equipped a point source‐influenced headwater catchment with a comprehensive measurement setup, to directly trace the different hydrochemical signals. Statistical approaches were used to address c‐Q relationships and hydrochemical drivers for nutrient export upstream, downstream and within the WWTP during baseflow conditions. Groundwater infiltration into the old and leaky sewer system as well as rainwater collected via the combined sewer system were found to significantly alter processes within the WWTP, resulting in highly variable effluent nutrient concentrations. Ammonium introduced by the WWTP is rapidly transformed in the stream, leading to increasing nitrate concentrations further downstream. The combination of processes introduced by the WWTP overlap the dilution and (non‐significant) chemostatic patterns of the upstream nitrate‐discharge relationship, leading to enrichment patterns shortly after, and mainly diluting patterns 290 m downstream of the WWTP. Regarding maximum nutrient concentrations, dry periods during autumn were particularly critical, as the WWTP introduced high ammonium concentrations, which coincided with high nitrate concentrations from the catchment and a minimal dilution potential of the stream. Our study demonstrates the importance of incorporating all nutrient sources into catchment analyses, to facilitate successful management decisions. Plain Language Summary Monitoring of point sources in rural areas, such as communal wastewater treatment plants, is often not very detailed. This makes it difficult to understand how they affect the water in streams. To fill that research gap, we installed a monitoring system in a rural catchment were a point source is located. We assessed water quality and quantity upstream, downstream and in the effluent. Leaky sewers and infiltrating groundwater probably influence the cleaning processes in the treatment plant, leading to varying nitrogen concentrations throughout the year. The mix of wastewater and upstream water creates a new chemical signal downstream of the wastewater treatment plant. This signal is additionally altered by ammonium, which is quickly transformed into nitrate as soon as it reaches the stream. In the fall, when stream water levels are low and can't dilute the effluent, the highest nitrogen concentration can be measured in the stream. Key Points The point source alters the dynamics of the nitrate‐c‐Q relationship observed upstream of the WWTP, especially during low flow conditions Groundwater infiltration into sewer system accounts for >60% of sewer water and can lead to variable water quality of the WWTP effluent Highest catchment NO3‐N concentrations and highest effluent NH4‐N concentrations coincide when stream dilution potential is minimal